Molecular characterization of MicroRNA-silenced TNL-1 (MIST1) and its role in plant defense - Del Espino Pérez, Ángel; López-Márquez, Diego; López-Pagán, Nieves; Rodríguez-Bejarano, Eduardo; Ruiz-Albert, Francisco Javier; Beuzón-López, Carmen del Rosario (My University, 2022)
miRNAs are sequence-dependent negative regulators of gene expression involved in many relevant plant processes, including immunity. Activation of defence genes can negatively impact plant fitness, and thus needs to be fine-tuned. miRNA-mediated regulation of gene expression is mediated by the activity of DCL proteins that induce cleavage of target transcripts. We have described miR825-5p as involved in the regulation of immunity. This miRNA specifically targets R genes of the TNL family. We have characterized the regulatory system formed by miRNA825-5p and its main target MIST1. This miRNA only triggers the RDR6-DCL4-dependent production of phasiRNAs from MIST1. MIST1 is the NLR gene from which the most phasiRNAs are produced in Arabidopsis. We reported that pri-miR825 is down-regulated after PAMP-perception and demonstrated that plants with altered levels of miR825-5p exhibit altered PTI-associated phenotypes. In addition, MIST1 has been described to be regulated by other mechanisms like nonsense mediated decay or polyubiquitination. We have characterized the expression pattern of both MIR825 and MIST1 and are currently studying the putative molecular role of MIST1 in defence apart from its demonstrated role as a miRNA825-5p-linked regulatory hub for TNLs regulation in Arabidopsis thaliana.
Keywords: Plantas - Defensas - Congresos; Ácido ribonucleico - Congresos; Arabidopsis thaliana - Congresos; miRNA; Defensa; Plantas; Regulación; Resistencia